Does Social Media User Engagement Impact Brand Preference? Exploring the Interactive Roles of Self-Brand Congruence and Perceived Social Approval - Onasanya, Yoyinsola Arinola (Curtin University, 2019)
This research study explores social media user engagement and its relationship with brand preference. Furthermore, the mediating role of social approval in this relationship and the moderating effect of consumers’ self- brand congruence on the association between social media user engagement and social approval are examined. Using an abductive approach, the hypotheses of this study are tested. The findings provide an insight into how consumers on social media platforms, develop their brand preferences.